The Intertemporal Role of Respiratory Support in Improving Neonatal Outcomes: A Narrative Review - Kosmas Sarafidis; William Chotas; Eleni Agakidou; Paraskevi Karagianni; Vasiliki Drossou (MDPI AG, 2021)
Defining improvements in healthcare can be challenging due to the need to assess multiple outcomes and measures. In neonates, although progress in respiratory support has been a key factor in improving survival, the same degree of improvement has not been documented in certain outcomes, such as bronchopulmonary dysplasia. By exploring the evolution of neonatal respiratory care over the last 60 years, this review highlights not only the scientific advances that occurred with the application of invasive mechanical ventilation but also the weakness of the existing knowledge. The contributing role of non-invasive ventilation and less-invasive surfactant administration methods as well as of certain pharmacological therapies is also discussed. Moreover, we analyze the cost-benefit of neonatal care-respiratory support and present future challenges and perspectives.